Temporal variations of larval digenean assemblages parasitizing Heleobia Parchappii (Mollusca: Cochliopidae) in two shallow lakes from the Buenos Aires province, Argentina - Merlo, Matias Javier (2019)
The larval digenean assemblages in snail hosts are influenced by biotic and abiotic factors and by environmental disturbances due to human activities. Given their susceptibility to different types of impact, they can be useful tools for the study of temporal variations in parasite communities. The study of temporal dynamics in prevalence and species richness of larval digenean assemblages of Heleobia parchappii (D’Orbigny, 1835), in two Pampean lakes, provides a good opportunity to test the supposition that seasonal variations in digenean assemblages are determined by a series of biotic and abiotic factors that operate interdependently. To analyze the temporal variations, and to evaluate how local factors influence these digenean assemblages in Los Padres and La Brava lakes (Buenos Aires province, Argentina), 2,400 specimens of H. parchappii were collected seasonally, during one year. The digenean assemblages in Los Padres and La Brava lakes were composed of 13 and 12 species respectively. These larval digenean assemblages showed similarities in the number and in the seasonal frequency of occurrence of species (eight of which were present in both lakes). However, despite these similarities, the assemblages showed different temporal dynamics in La Brava and Los Padres lakes and, also, different correlations with the abiotic and biotic factors analyzed during this study (temperature, high of the water column and snail relative abundance). Temporal dynamics in prevalence and species richness of larval digenean assemblages of H. parchappii in both lakes seems to be influenced by a series of factors (diversity and abundance of definitive hosts, intermediate and definitive host location, snail relative abundance and anthropogenic disturbances). Our results highlight the importance of analyzing the role and interaction of local factors, especially in studies dealing with spatiotemporal fluctuations or with distance decay of similarities in species richness of parasite assemblages.